2008
DOI: 10.1097/scs.0b013e318184365d
|View full text |Cite
|
Sign up to set email alerts
|

Distraction Osteogenesis in the Management of Severe Maxillary Hypoplasia in Cleft Lip and Palate Patients

Abstract: The aim of this study was to systematically review literature reporting on the use of external distraction osteogenesis (DO) and internal DO in the treatment of severe maxillary hypoplasia in cleft and palate patients. Literature research has been performed using the PubMed database of the National Library of Medicine and National Institutes of Health from 1966 to August 2007. We used cleft lip and palate and distraction osteogenesis as key words. Of the 104 articles found, we only considered the Anglo-Saxon l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 72 publications
1
72
0
5
Order By: Relevance
“…Extensive morphologic studies have demonstrated these skeletal and/or dental deficiencies present in the anteroposterior (AP), vertical, and transverse dimensions in the early stages of pediatric growth ( € Oztürk and Cura, 1996;Schneiderman et al, 2009;Abuhijleh et al, 2014). Therefore, instead of waiting until skeletal maturity, midfacial hypoplasia have been early treated in growing patients because of psychological, functional, and esthetic concerns (Ho et al, 2006;Scolozzi, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive morphologic studies have demonstrated these skeletal and/or dental deficiencies present in the anteroposterior (AP), vertical, and transverse dimensions in the early stages of pediatric growth ( € Oztürk and Cura, 1996;Schneiderman et al, 2009;Abuhijleh et al, 2014). Therefore, instead of waiting until skeletal maturity, midfacial hypoplasia have been early treated in growing patients because of psychological, functional, and esthetic concerns (Ho et al, 2006;Scolozzi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The early treatment options for midfacial hypoplasia mainly include distraction osteogenesis (DO) with Le Fort osteotomy (Scolozzi, 2008) and trans-sutural distraction osteogenesis (TSDO) (Liu et al, 2005;Tong et al, 2015), which both progressively advance the skeleton in association with the expansion of the surrounding soft tissue. TSDO has been proved to have the advantage of achieving the advancement of midfacial skeleton by applying force to the immature circummaxillary sutures while successfully avoiding the risk of Le Fort osteotomy in some way, but there is still lack of recognition of the mechanism of the TSDO in growing CLP patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ross et al (1989) showed that about 25% of patients with unilateral cleft lip and palate develop maxillary hypoplasia that does not respond to orthodontic treatment alone [3]. Moreover, as a result of the severe maxillary hypoplasia, the mandible often undergoes anterior and superior autorotation with subsequent overclosure of the vertical dimension, resulting in a loss of facial height, pseudoprognathism, and upward inclination of the occlusal plane [4].…”
Section: Introductionmentioning
confidence: 99%
“…Mais de 25% desses indivíduos irão desenvolver uma significativa hipoplasia maxilar e fatalmente se submeterão a osteotomia maxilar, técnica mais utilizada para solucionar essa deficiência de crescimento. (THONGDEE et al, 2005;SCOLOZZI et al, 2008).…”
Section: Ao Professor Doutor E Meu Co-orientador Renato Yassutakaunclassified
“…A possibilidade de uma recidiva cirúrgica é significativa, e poderá fazer com que o paciente retorne a uma condição estética e funcional desagradável (THONGDEE et al, 2005;SCOLOZZI et al, 2008).…”
Section: Ao Professor Doutor E Meu Co-orientador Renato Yassutakaunclassified